LPG gas leak security system using Microcontroller based Android application - Fauzi, Rahmad; Islami, Ta ali; Maulana, Ricky; Ranuharja, Fadli (Department of Electrical Engineering Universitas Negeri Padang, 2024)
The use of Liquid Petroleum Gas (LPG) among Indonesian people continues to increase from year to year. One of the causes of this condition is kerosene which is scarce and difficult to obtain. However, the recent increase in fires and accidents caused by leaking and exploding LPG gas cylinders has become a frightening thing for people who use this gas. LPG gas is known for its flammable nature so leaks from LPG equipment pose a high risk of fire. Due to its sensitive nature, special attention needs to be paid to this type of fuel. This research aims to produce a design for a leak detection tool for LPG gas cylinders via an Android smartphone. This research uses experimental methods to ensure the suitability of the resulting tools to the expected standards. The test results show that the results of design and testing, this microcontroller-based LPG gas leak detection tool using an Android application shows effectiveness in detecting gas leaks at dangerous levels and is able to provide early warning to users. This tool can identify various gas concentration levels through the MQ-2 sensor and send notifications to the mobile application when the gas content exceeds safe limits.